Mapping the landscape of marketing technology: trends, theories and trajectories in ecosystem research - Noptanit Chotisarn; Thadathibesra Phuthong (Cogent Business & Management)
The marketing technology ecosystem is rapidly evolving, integrating digital tools and platforms to transform marketing practices. This study analyses this dynamic and diverse field, addressing research trends, theoretical foundations and future directions. This research uses a multimethod approach combining bibliometric analysis, systematic literature review and content analysis. The study analyzed 144 articles from 2017 to 2024, using the theory, context, characteristics and method (TCCM) framework to structure the findings. Key research themes include artificial intelligence (AI), blockchain, digital marketing and customer experience. Journals like Industrial Marketing Management dominate the field, with the United States and the United Kingdom (UK) leading in publications; theoretical foundations focus on service-dominant logic (SDL), digital transformation, and ecosystem perspectives. Commonly used theories include technology acceptance models and dynamic capabilities, applied across various industries and digital platforms. Research methods range from quantitative surveys to qualitative case studies and emerging AI-driven analytics. The study highlights the field’s rapid evolution and diverse, interdisciplinary nature, combining various perspectives and expertise. Exciting future research directions include integrating emerging technologies, exploring sustainability and ethical implications, and developing more sophisticated, multimethod approaches to capture the complexity of marketing technology ecosystems.